The detached locus encodes Drosophila Dystrophin, which acts with other components of the Dystrophin Associated Protein Complex to influence intercellular signalling in developing wing veins. - Christoforou, C.P.; Greer, C.E.; Challoner, B.R.; Charizanos, D.; Ray, R.P. (Developmental Biology, 2008)
Dystrophin and Dystroglycan are the two central components of the multimeric Dystrophin Associated Protein Complex, or DAPC, that is thought to provide a mechanical link between the extracellular matrix and the actin cytoskeleton, disruption of which leads to muscular dystrophy in humans. We present the characterization of the Drosophila 'crossveinless' mutation detached (det), and show that the gene encodes the fly ortholog of Dystrophin. Our genetic analysis shows that, in flies, Dystrophin is a non-essential gene, and the sole overt morphological defect associated with null mutations in the locus is the variable loss of the posterior crossvein that has been described for alleles of det. Null mutations in Drosophila Dystroglycan (Dg) are similarly viable and exhibit this crossvein defect, indicating that both of the central DAPC components have been co-opted for this atypical function of the complex. In the developing wing, the Drosophila DAPC affects the intercellular signalling pathways involved in vein specification. In det and Dg mutant wings, the early BMP signalling that initiates crossvein specification is not maintained, particularly in the pro-vein territories adjacent to the longitudinal veins, and this results in the production of a crossvein fragment in the intervein between the two longitudinal veins. Genetic interaction studies suggest that the DAPC may exert this effect indirectly by down-regulating Notch signalling in pro-vein territories, leading to enhanced BMP signalling in the intervein by diffusion of BMP ligands from the longitudinal veins.